Meningkatkan Hasil Belajar Siswa Kelas IV menggunakan Metode Problem Based Learning dengan Media Video di UPT SDN Negeri 003 Pasaribu - Evi Farida Purba; Dicky Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The background of this study is the lack of optimal student learning outcomes at SDN 003 Pasaribu. There are these problems, so efforts are made to improve learning so that student learning outcomes can be improved through classroom action research. This Classroom Action Research (PTK) aims to improve the learning outcomes of grade IV students of SD Negeri 003 Pasaribu through the application of the Problem Based Learning model with the help of videos. The data collection technique uses a learning outcome test (post-test) and an attitude observation sheet according to the dimensions of the Pancasila Student Profile; namely Faith, Fear of God Almighty, and Noble Character, Global Diversity, Mutual Cooperation, Independence, Critical Reasoning, Creative. The results show that the application of the PBL model can improve student learning outcomes as shown through the comparison of post-test scores in cycles I and II. Thus, the PBL model has proven to be effective in improving the learning outcomes of grade IV students of SD Negeri 003 Pasaribu.